Hubungan Antara Kedekatan dan Lama Domisili Di Sekitar TPA Kebon Kongok Desa Suka Makmur Gerung NTB Dengan Arus Puncak Ekspirasi Pada Ibu Rumah Tangga - Hafidz Reginald Bhagaskara; Risky Irawan Putra Priono; Sabrina Intan Zoraya; I Gusti Putu Winangun (Universitas Pahlawan Tuanku Tambusai, 2023)
Peak Expiratory Flow (PEF) is a simple measurement of the maximal flow rate achieved during a strong expiration following a full inspiration. PEF is used as an indicator of lung function. Decreased lung function can be caused by gases emitted from landfill sites. TPA Kebon Kongok is the largest landfill in the province of NTB, which has been operating since 1993. The landfill used open dumping system for a long time before switching to sanitary landfill in 2021. This situation can lead to gas exposure for residents living near the landfill, especially for housewives who spend a lot of time at home. Therefore, this study aims to investigate the relationship between proximity and length of residency around TPA and PEF in housewives. The study was conducted in Suka Makmur village by comparing two hamlets near and far from the landfill. The nearest hamlet (0-1 km) from the landfill was Kedatuk, while the farthest hamlet (1-2 km) was Ketejer. The study used a cross-sectional design with proportionate stratified random sampling technique. The total sample in this study was 183, consisting of 110 samples from the near hamlet of Kedatuk and 73 samples from the far hamlet of Ketejer.There was a significant statistical relationship between proximity to the landfill and PEF (p-value 0.001), while there was no significant relationship between length of residency and PEF (p-value 0.421).There is a significant relationship between proximity to the landfill and PEF, while there is no significant relationship between length of residency and PEF.